In vitro sytotoxic activities of triterpene glycosides of Stichopus chloronotus and the extracts of other Malaysian sea cucumbers - Althunibat, Osama Y. (Kulliyyah of Science, International Islamic University Malaysia, 2012)
Discovery and development of new anticancer drugs remain one of the most challenging areas in recent biomedical researches. With regard to this matter, isolation and identification of cytotoxic compounds from natural sources have led the development of chemotherapeutic drugs for several decades. Sea cucumbers are marine invertebrates in which some species have been proposed as promising sources for cytotoxic and antioxidant materials. Therefore, this study aimed to investigate the presence of new potential antioxidant and/or cytotoxic compounds in different species of Malaysian sea cucumbers. In the first stage of the study, cytotoxic and antioxidant activities were screened in aqueous and organic extracts of seven local sea cucumber species, i.e. Molpadia sp, Holothuria leucospilota, H. scabra, H. edulis, H. atra, Stichopus chloronotus and S. horrens, by using in vitro assays. The results of this stage revealed that the aqueous extracts showed higher antioxidant activities (DPPH IC5o 2.0-10.0 mg/mL), meanwhile the organic extracts of the tested sea cucumber species exhibited more potent cytotoxic effects (IC5o 3.0-39.0 μg/mL). In general, the tested species exhibited more promising cytotoxic than antioxidant properties, where S. chloronotus was found to be the most active species (IC50 6.0-70.0 μg/mL). Therefore, the second stage of the study aimed to isolate the active cytotoxic compounds from this species and to identify their structures. The isolation process was performed through successive steps of various chromatographic methods which had been guided by the cytotoxic activities of the separated fractions and subfractions. Three new cytotoxic glycosides (A, B, and C) were sucessfully isolated from butanol fraction of th is species. The final structures of the isolated glycosides were established with the aid of various spectroscopic analysis including infra red (IR) absorption, one and two dimension at nuclear magnetic resonance (NMR) and mass spectrometry (MS). Based on the above analysis, the structures of the isolated compounds were concluded as triterpene glycosides composed of holostane-type triterpene that attached to various sulphated hexasaccharide units. The molecular formula of glycoside A was identified as C66 H 1o4Na20 36S2 (calculated molecular weight= 1583.62 Da), glycoside B was C66H103Na3040S3 (MW= 1701.66 Da), and glycoside C was C66H100Na4043S4 (MW= 1801.69 Da). The three isolated glycosides (A, B, and C) exhibited potential cytotoxic effects against various cancer cell lines, where glycoside C was found to be the most potent compound (IC 5o = 0.9-2.4 μM), followed by B (IC 50 = 1.3-2.9 μM) and A (IC5o = 2.4-7.5 μM). Subsequently, the mechanism of cell death induced by the isolated compounds was demonstrated in the last stage of the research. After performing various morphological, biochemical and molecular assessments, it was established that the isolated compounds induce cell death through triggering necrosis which is mediated by overproduction of reactive oxygen species (ROS). In conclusion, the present study has revealed the cytotoxic potentials of Malaysian sea cucumbers. The three new cytotoxic compounds isolated in this study may lead to the development of new anticancer agents.